A typology of cooperation strategies in the telecommunication industry: An exploratory analysis and theoretical foundations - Felix Limbach; Jochen Wulf; Rüdiger Zarnekow; Michael Düser (International Telecommunications Society (ITS), 2011)
The value chain of the telecommunication industry is subject to a continuing disintegration which is caused by outsourced network operation, the provisioning of wholesale interfaces to competing service providers and the cooperative provisioning of broadband access. Thus, many companies regard cooperation as an element of cooperate strategy. In this paper we propose a cooperation topology for the telecommunication industry and identify drivers of cooperation based on the assessment of case studies. The results indicate that drivers of cooperation differ with respect to the cooperation direction and that the combination of complementary resources is the dominating driver of cooperation.
Keywords: B40; A10; D80; O33; 330; Cooperation; telecommunication; typology of cooperation strategies; transaction costs